New Record of Naucorids (Hemiptera:Heteroptera) in India - and Ramesh Chandra3, Mohammad Shoeb1, Nasim Jahan2, (Recent Research in Science and Technology, 2011)
The Naucoridae are most interesting and fascinating aquatic water bugs known as water creepers, needle bugs and toebiters. In view of the studies of Naucoridae fauna from other parts of world, the study of Indian Naucoridae is of a great importance. The genus Naucoris is previously record by three species viz., Naucoris scutellaris Stal., 1859, Naucoris sordidus Distant, 1910 and Naucoris vividus Distant, 1910. A new species of the genus are being for the first brought to the knowledge in present condition. The present work is an outcome of three and a half years continuous survey of these bugs from different parts of India. During the course of study a large number of bugs were collected from ponds, lakes, rivers, ditches, streams and water reservoirs of various ports of India. Several field surveys were undertaken in Uttar Pradesh, Punjab, Haryana, west Bengal, Assam, Delhi, Rajasthan, Madhya Pradesh, Himachal Pradesh, Tamil Nadu, Kerala, Karnataka, Jammu and Kashmir. The genital Propagation of the species was examined made and studied. The entire insects collected in the field were immediately preserved in 90% alcohol. The entire study was made under stereoscope, binoculars and compound microscope. The sketches were made with the help of camera lucida and all measurement was taken with micrometer.